Meta-analysis of the effect and clinical significance of Delphian lymph node metastasis in papillary thyroid cancer - Chen, Yan; Wang, YiHan; Li, Changlin; Zhang, XueYan; Fu, Yantao (Frontiers in Endocrinology, 2024)
Objective: To investigate the effect and clinical significance of Delphian lymph nodes (DLN) on the factors influencing papillary thyroid cancer (PTC) to provide individualized guidance for the surgical treatment of thyroid cancer. Methods: Relevant studies from PubMed, Web of Science, the Cochrane Library, Embase, and China National Knowledge Infrastructure databases were searched until February 13, 2023. Stringent selection parameters were used to obtain included data and homogeneous articles. Analyses were performed using Revman 5.4 and SPSS software. A P-value of < 0.05 was considered statistically significant. Results: Five studies were finally included in this study. The results revealed a higher risk of DLN metastasis (DLNM) in patients with tumor size >1cm, multifocality, and extrathyroidal extension (ETE) of the thyroid. The risk of central lymph node metastasis (CLNM) was 11.25 times higher in DLN-positive patients with PTC than in DLNnegative (OR = 11.25, 95% CI: 8.64-14.64, P < 0.05) patients. The risk of LLNM was 5.57 times higher in DLN-positive patients with PTC than in DLN-negative (OR = 5.57, 95% CI: 4.57-6.78, P < 0.001) patients. The risk of postoperative recurrence in DLNpositive patients with PTC was 3.49 times higher (OR = 3.49, 95% CI: 1.91-6.38, P < 0.001) than in DLN-negative patients with PTC. Conclusion: Patients with tumor size >1 cm in diameter, multifocality, and ETE have an increased risk for DLN development. DLN-positive patients with central and lateral cervical lymph node metastasis and postoperative recurrence are at higher risk than DLN-negative patients.